Routing protocols for hybrid wireless networks: a brief review - Miaad Husam Mahdi; Ibrahim Adel Ibrahim (Institute of Advanced Engineering and Science, 2022)
Hybrid wireless networks (HWNs) are resulted from the integration of a mobile Ad hoc networks (MANET) and an infrastructure wireless networks. These networks have received increasing interest from researchers for their superior performance and reliability. Packet routing protocols in hybrid wireless networks are important to increase the capacity and scalability of these networks, therefore, several routing protocols have been proposed. Routing protocols in HWNs are designed and implemented from combining the cellular transmission mode with the Ad hoc transmission mode. To route a message to the intended recipient of the sender, hybrid wireless networks use multi-hop technology. However, the source node needs relay nodes, which may be either adjacent nodes or base stations depending on set of parameters like bandwidth, load balancing, or the nearest node. This paper explores routing protocols for hybrid wireless networks and the techniques to enhance the security, performance, and capacity of these routing protocols.